Should liberals sometimes prefer dictatorships to democracies? A closer look at the Hayek thesis. Issue 3 (15th April 2016) - Knutsen, Tommy André
Abstract : Is liberal autocracy preferable to illiberal democracy, as Friedrich Hayek forcefully argued? This article examines two main problems with this argument. First, it seems counterintuitive for autocracies to be combined with liberalism, or for democracies to exist without essential liberal freedoms. Second, it is difficult to establish sound criteria for when a particular democracy is inferior to a given dictatorship. Since there is a difference between those types of liberal freedoms that are sometimes protected in dictatorships and those that are (almost) never protected, assessing the quality of liberties brings us closer to a solution on both issues. It is argued that whether an autocracy can be genuinely liberal, and whether liberals should sometimes prefer autocracy to democracy, depends on how we rank economic freedoms compared to other freedoms.